2004
DOI: 10.1128/jcm.42.7.3012-3016.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Serum and Liver Hepatitis C Virus RNA Levels in Patients Coinfected with Human Immunodeficiency Virus and Treated with Antiretroviral Drugs

Abstract: We examined hepatitis C virus (HCV) RNA levels in serum, peripheral blood mononuclear cells (PBMC), and the liver for 135 patients with chronic HCV infections, 44 of whom were human immunodeficiency virus (HIV) positive and treated with highly active antiretroviral therapy (group A), 66 of whom were HIV negative (group B), with abnormal serum alanine aminotransferase (ALT) values, and 25 of whom were HIV negative, with ALT values of <1.5 times the normal value (group C). Patients had not been treated with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…Although the present study found that plasma and cell-associated HCV RNA are subject to some common constraints, the relatively low strength of their correlations suggests, in accordance with the results of previous reports [36][37][38], differential regulation of PBMC-associated HCV RNA, by as-yetunknown host-or virus-specific factors. In contrast, proportions of cell-associated HCV RNA load versus plasma HCV RNA load were observed to be patient specific and relatively stable over time.…”
Section: Discussionsupporting
confidence: 88%
“…Although the present study found that plasma and cell-associated HCV RNA are subject to some common constraints, the relatively low strength of their correlations suggests, in accordance with the results of previous reports [36][37][38], differential regulation of PBMC-associated HCV RNA, by as-yetunknown host-or virus-specific factors. In contrast, proportions of cell-associated HCV RNA load versus plasma HCV RNA load were observed to be patient specific and relatively stable over time.…”
Section: Discussionsupporting
confidence: 88%
“…This result was not surprising given the normal levels of CD4 cell count in our HIV-infected population [6] . However besides plasma viral load, the detection of HCV infection in cellular subpopulations of the peripheral blood was important [33] and able to discriminate substantial differences between HCV monoinfected and HIV-HCV coinfected patients. Whereas there is little doubt that HCV replicates primarily in the liver, the presence of extrahepatic replication sites remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Uma análise posterior de 21 pacientes desse mesmo estudo (60) (60) acredita que fatores farmacocinéticos possam justificá-los e assim, o modelo cinético alterado também poderá ser útil para outros Interferons. Segundo Shudo (73) (20) . (81,62,72,71) .…”
Section: Discriminação Total De Pacientesunclassified